Kenya Climate Smart Agriculture (CSA) Multi-Stakeholder Platform Strategic Plan (MSP) 2022-2026 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The aim of the MSP is to promote an inclusive institutional framework for coordination and harmonization of CSA implementation while fostering an enabling environment for the realization of CSA objectives.